Theoretical aspects of modeling fuzzy controller for management system of electric energy consumption by airports - Лещинський, Олег Львович; Бугайко, Дмитро Олександрович; Соколова, Наталія Петрівна (Eastern-European Journal of Enterprise Technologies, 2014)
The paper deals with the use of the management models of effective electric energy consumption by airports with fuzzy controller. The implementation variants of fuzzy controllers are considered. According to the fuzzy control analysis, based on existing fuzzy controllers, appropriate models and expressions of transfer functions are proposed. Studies show that fuzzy models are universal approximators for systems that are modeled, i.e. they can be used to obtain approximate representations of systems with arbitrary preset accuracy. Use of this controller will allow to improve the quality of the modeling system of energy efficiency of airlines, which is extremely important in economic crisis conditions and is of practical importance for improving the economic security of the airport. Permanent monitoring of electric energy consumption by airports taking into account features of equipment and operation modes of facilities will allow to get practical recommendations on high-quality management of electric energy consumption efficiency in order to improve energy security.